(untitled) (Bangladesh Journal of Agricultural Research, 2017)
The study was conducted for assessing postharvest loss of major fruits in different hill regions of Bangladesh. The study areas covered four hill districts, namely Rangamati, Khagrachari, Bandarban and Moulvibazar and six selected fruits, namely mango, jackfruit, litchi, banana, pineapple and orange. These fruits are grown intensively in hill regions compared to other parts of Bangladesh. Data were collected from 2050 fruit growers and 749 traders of eight (8) upazilas considering accessible and less accessible areas. At farmers and traders level, the total postharvest loss of banana, pineapple, orange, mango, litchi and jackfruit were 372, 274, 200, 243, 165 and 380 kg/mt which was accounted about 37%, 27%, 20%, 24%, 17% and 38% of total production respectively. The main postharvest losses at farm level were incurred due to severe attack of insect, bat, squirrel and monkey. For traders, major losses were incurred during transportation. On the basis of retail price, the annual economic loss was estimated as Tk. 2107.5 crore and the maximum loss was incurred for banana (Tk. 705.79 crore) followed by pineapple (Tk. 550.58 crore) and mango (Tk. 508.95 crore) and the lowest for orange (Tk. 1.12 crore). It is interesting to note that, transportation dummy, labour dummy and market demand dummy had negative and significant effect on the postharvest losses. If transportation facilities can be improved and market demand and labour availability can be increased, postharvest loss will be decreased to an acceptable level at the study areas. Bangladesh J. Agril. Res. 42(1): 171-184, March 2017